Pengaruh Motivasi Intrinsik Dan Ekstrinsik Terhadap Prestasi Kerja Dengan Komitmen Sebagai Variabel Intervening - Merryana Damaris Polly; Rahmat Laan; Burhannudin Gesi (Jurnal Manajemen, 2019)
The purpose of this study is to determine the role of mediationbetween the influence of intrinsic and extrinsic motivation on workperformance. The number of samples studied was 45 employeeswith a withdrawal technique using saturated samples. The maininstrument of data collection was a questionnaire. Data analysisuses multiple regression techniques. The results showedcommitment plays a role in mediating the influence betweenintrinsic and extrinsic mitivation on employee work performance.